Design and manufacture of parts and assemblies of aerospace structures made of composite materials in conditions of additive manufacturing - A. O. Firsin; R. A. Vdovin; E. S. Goncharov; I. D. Markanov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This article raises the topic of modernization of existing technological processes of procurement production in terms of eliminating the expensive and lengthy stage of designing and manufacturing metal molds and the introduction of 3D printing technologies. The article provides information about 3D printing technology based on the extrusion method. Information is provided on the main stages of designing the tooling for the «Insert» part, taking into account the features and limitations associated with printing on 3D printers. As part of the study, the roughness and shrinkage of test samples are analyzed, which are made on a 3D printer from various composite materials.